1975
DOI: 10.1111/j.1600-0714.1975.tb01748.x
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of salivary substances with bacteria

Abstract: Abstract. Reactions between selected strains of oral streptococci and saliva were studied spectrophotometrically. The curves of absorbance (700 nm) versus those of time were sigmoidal for aggregating saliva‐bacteria mixtures. When the logarithm of the ratio of the change in absorbance to the remaining absorbance was plotted against the reaction time, straight lines were obtained. At a fixed concentration of bacteria, the slope of these lines for a series of dilutions of a selected saliva sample was a parabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
1

Year Published

1978
1978
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 10 publications
7
76
1
Order By: Relevance
“…coli, presumably via N-acetyl-glucosamine and/or L-glycero-D-manno-heptose residues associated with core oligosaccharides. In other studies, Kuhlman et al (13) showed that serum MBP binds to mannose-rich 0-poly-+ Adsorbed BAL saccharides on the surface ofwild-type Salmonella montevideo ;orbance 1.0 has been extensively studied in the context of oral microbes BAL or with 3 and saliva (22,31), and there appear to be several types of affinity chrosalivary proteins that can mediate bacterial agglutination. e was adjusted Among these is a group of nonimmunoglobulin, nonmucous ubations were salivary agglutinins with conglutinin-like activity (32,33 (3) and are also consistent with protein biochemical studies that indie calcium-in-cate that SP-D is assembled as tetramers of trimers, similar to )served sugar bovine conglutinin (2,4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…coli, presumably via N-acetyl-glucosamine and/or L-glycero-D-manno-heptose residues associated with core oligosaccharides. In other studies, Kuhlman et al (13) showed that serum MBP binds to mannose-rich 0-poly-+ Adsorbed BAL saccharides on the surface ofwild-type Salmonella montevideo ;orbance 1.0 has been extensively studied in the context of oral microbes BAL or with 3 and saliva (22,31), and there appear to be several types of affinity chrosalivary proteins that can mediate bacterial agglutination. e was adjusted Among these is a group of nonimmunoglobulin, nonmucous ubations were salivary agglutinins with conglutinin-like activity (32,33 (3) and are also consistent with protein biochemical studies that indie calcium-in-cate that SP-D is assembled as tetramers of trimers, similar to )served sugar bovine conglutinin (2,4).…”
Section: Discussionmentioning
confidence: 99%
“…The time course of macroscopic bacterial agglutination was monitored using a spectrophotometric sedimentation assay modified from Ericson et al (22). Stock solutions of bacteria were prepared in HBS (OD700nm = 1.0).…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary results from our laboratory suggest that mucin may be involved in the observed P. aeruginosa aggregation, as shown by ongoing immunocytochemical studies using a monoclonal antibody 17 B. developed using purified large molecular weight macromolecules of rhesus monkey tracheal secretion as immunogen (24,25), kindly supplied by Dr. R. Wu (California Primate Research Center, University of California). Mucin-like glycoproteins present in saliva are known to induce the aggregation oforal bacteria (26,27). Bacterial aggregation in the respiratory tract may be of great in vivo significance since large aggregates are supposed to be cleared more easily by the mucociliary transport than individual organisms.…”
Section: Discussionmentioning
confidence: 99%
“…To remove EDTA and glutathione prior to the assay, P. carinii suspensions were twice centrifuged at 1,000 ϫ g for 10 min at 4°C, resuspended with TBS (50 mM Tris HCl-150 mM NaCl [pH 7.4]), and adjusted to a concentration of 7.5 ϫ 10 6 P. carinii organisms per ml. The subsequent aggregation of P. carinii was quantified by using a modification of the spectrophotometric sedimentation assay of Ericson and coworkers (14,28). The time course of macroscopic P. carinii agglutination was monitored using a spectrophotometer (model DU-74; Beckman Coulter Inc., Fullerton, Calif.) at a 700-nm wavelength (measuring optical density at 700 nm [OD 700 ]).…”
Section: Methodsmentioning
confidence: 99%